Media & The News - Holly Duhig (India Booklife, 2018)
This exciting series gives readers their first taste of some of the most important values in today's world. Here children can explore what it means to be part of a society and discover the cultural and spiritual diversity that life has to offer.This exciting series gives readers their first taste of some of the most important values in today's world. Here children can explore what it means to be part of a society and discover the cultural and spiritual diversity that life has to offer.
Keywords: How We Express Ourselves -- -Media; How We Organize Ourselves -- -Digital Media